2006
DOI: 10.1038/sj.ijo.0803501
|View full text |Cite
|
Sign up to set email alerts
|

Disordered eating behaviours and cognitions in young women with obesity: relationship with psychological status

Abstract: Objective: To examine levels of eating disorder behaviours and cognitions of young women with obesity in the Australian Capital Territory, Australia and assess the impact upon psychological status. Design: General population cross-sectional survey. Subjects: A total of 4891 young women from the community aged 18-42 years, of which 630 were in the obese weight range. Measurements: Body mass index (BMI), eating disorder psychopathology (eating disorder examination questionnaire), and psychological distress (K-10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
58
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(64 citation statements)
references
References 42 publications
5
58
0
1
Order By: Relevance
“…Positive, but rather small relationships have been found between BMI and binge eating severity in samples with diverse body weight [45][46][47]. Higher binge eating frequency could be found in obese as compared to non-obese women [48]. This positive association between BMI and binge eating seems to be vanished within obese samples.…”
Section: Binge Eating and Bmimentioning
confidence: 94%
“…Positive, but rather small relationships have been found between BMI and binge eating severity in samples with diverse body weight [45][46][47]. Higher binge eating frequency could be found in obese as compared to non-obese women [48]. This positive association between BMI and binge eating seems to be vanished within obese samples.…”
Section: Binge Eating and Bmimentioning
confidence: 94%
“…Objectification theory (Fredrickson and Roberts 1997) was used to shape the design of the current study, which examined this association across the adult lifespan for both women and men in Australia. Body dissatisfaction has been linked with a range of adverse psychosocial consequences, including poor self-esteem, depression, eating disorders and obesity (Darby et al 2007;Stice 2002;Wiederman and Pryor 2000). Therefore, we also aimed to evaluate, using a short-term longitudinal design, whether the direction of the relationship between body dissatisfaction and global evaluations of self-worth declines with age for either or both genders, after accounting for other areas of life satisfaction.…”
Section: Introductionmentioning
confidence: 98%
“…6 It is only in the past decade that the significance of comorbidity between obesity and eating disorder behavior has been recognized, following the introduction of binge eating disorder as a provisional diagnosis requiring further research in DSM-IV. 7 Research on adolescent girls 8 and adult women 9 has found those suffering obesity have high rates of ED behaviors such as binge eating, fasting, diet pill use, laxative misuse, diuretic misuse, and self induced vomiting. Other cross-sectional studies have focused on the comorbidity of binge eating, binge eating disorder and obesity, as it has been found that binge eating may contribute to the development of obesity.…”
Section: Introductionmentioning
confidence: 99%